A Metaphorical Approach to the Execution of Management Roles - Rodríguez Revelo, Elsy (2020)
Metaphors allow us to describe implicit practices associated with management roles when having to contend with complex contexts not addressed by educational regulations and policies, as identified in Spain. Thus, this study endeavors to uncover the roles of school principals in the city of Zaragoza, Spain. This is a qualitative study with a multiple-case design backed by techniques such as non-participatory observation, document analysis, in-depth interviews and discussion groups. The results reveal the different roles of principals when responding to specific student needs, which also directly and indirectly impacts how the schools is managed. The study does not claim to be representative of similar contexts for the three school cases that were analyzed.  Nevertheless, it is important to understand the management function framework in order to extrapolate it to similar scenarios. The spirit of this study is to describe and understand the current scenario to, ultimately be able to uncover it. Thus, the approach must be that of reflecting on the repercussions when executing management functions amidst similar contexts of social adversity.